The influence of tolerance, prosocial behavior, cultural openness, and social identity on attitude towards tourists: a quantitative study among local residents in Yogyakarta, Indonesia - Budiutami, Giannisa Novi; Ma’rof, Aini Azeqa; Abdullah, Haslinda; Kunasekaran, Puvaneswaran (Human Resource Management Academic Research Society, 2024)
Tourism growth in culturally rich destinations like Yogyakarta, Indonesia, brings both opportunities and challenges, necessitating harmonious local-tourist relations. This study explores the influence of tolerance, prosocial behavior, cultural openness, and social identity on attitude towards tourists among local residents. A sample of 434 participants was analyzed using quantitative methods, including Pearson correlation and multiple regression analyses performed in SPSS. The results revealed that tolerance was the strongest predictor of positive attitude towards tourists, followed by prosocial behavior, cultural openness, and social identity. These findings highlight the critical role of fostering tolerance and cultural openness, alongside prosocial behaviors, in promoting positive perceptions of tourists. The insights derived from this research offer valuable guidance for community leaders, policymakers, and tourism authorities aiming to enhance sustainable tourism development in Yogyakarta.